2020
DOI: 10.1002/ppsc.201900433
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared‐Absorbing Diketopyrrolopyrrole‐Based Semiconducting Polymer Nanoparticles for Photothermal Therapy

Abstract: Photothermal therapy, an excellent therapeutic approach, has received much attention in recent years. Herein, a novel diketopyrrolopyrrole polymer (DPP‐BDP) is prepared, which shows intense near‐infrared (NIR) optical absorption and admirable photothermal conversion efficacy. Impressively, after assembly into nanoparticles (DB‐FA), the as‐prepared conjugated polymer demonstrates a uniformly distributed size around 200 nm with remarkable NIR absorption at 808 nm. Additionally, it displays high biocompatibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Recently, the synthesis and application prospects of a DPP-based polymer (P153-NP) exhibiting a 99.2% tumor inhibition rate at 808 nm irradiation were reported by Deng et al 65 A uniformly distributed particle size of approximately 200 nm was observed for P153-NP's. P153-NP's exhibited high biocompatibility and photostability, indicating that these could be potentially used in the field of anticancer phototherapy.…”
Section: Dpp-derived Polymers For Pttmentioning
confidence: 99%
“…Recently, the synthesis and application prospects of a DPP-based polymer (P153-NP) exhibiting a 99.2% tumor inhibition rate at 808 nm irradiation were reported by Deng et al 65 A uniformly distributed particle size of approximately 200 nm was observed for P153-NP's. P153-NP's exhibited high biocompatibility and photostability, indicating that these could be potentially used in the field of anticancer phototherapy.…”
Section: Dpp-derived Polymers For Pttmentioning
confidence: 99%
“…In analogy to nanoprecipitation method, the resulting NPs size depends on the nature and concentration of the polymer and surfactant employed, stirring methodology, emulsion temperature, selected organic solvent, etc. Miniemulsion techniques are commonly utilized when PTs are not fully soluble in a water‐mixable solvent 63–65 . In general, the obtained NPs have a size in the range 30‐500 nm, and a layer of surfactants always stabilizes their surface.…”
Section: Synthesis Of Semiconducting Pt‐npsmentioning
confidence: 99%
“…Push‐pull PT‐based NPs possessing absorbance in the NIR‐I optical window (700‐900 nm) have been widely explored by many research groups to selectively ablate tumors with minimal invasiveness and low toxicity to normal tissues 65 . For example, Li et al reported the preparation of small‐sized NPs (∼30 nm) using polymers containing diketopyrrolopyrrole (A) bridged with different thiophene units (D), which exhibit NIR absorption between 600 nm and 900 nm 157 .…”
Section: Biological Applications Of Pt‐npsmentioning
confidence: 99%
“…In fact, DPP derivatives have applications in materials technology, from paint pigments to dye-sensitized solar cells (DSSC) [ 2 , 3 , 4 , 5 , 6 ], organic solar cells [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ], organic electronics [ 14 , 15 , 16 , 17 ], fluorescent probes [ 18 , 19 , 20 , 21 , 22 , 23 ], materials for lithium-ion batteries [ 24 ], for ionic charge storage [ 25 ], or for the removal of micropollutants from water [ 26 ], etc. Besides that, the studies concerning their potential use in biological applications, namely as antibacterial agents [ 27 , 28 , 29 ], in photodynamic/photothermal therapy [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], or bioimaging/theranostics [ 39 , 40 , 41 , 42 , 43 ], have increased in recent years.…”
Section: Introductionmentioning
confidence: 99%